1999
DOI: 10.1002/ep.670180119
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical fluid process for removal of polychlorodibenzodioxin and dibenzofuran from fly ash

Abstract: A process is proposed for the decontamination of fly ash from an urban solid‐waste incineration facility (USWI), where the target contaminants are polychlorodibenzodioxins (PCDDs) and dibenzofurans (PCDFs), a class of highly toxic tricyclo‐polychlorinated organics. In general, the ash waste requires inertization and disposal into a controlled landfill. Here, we propose an inertization process based on the reduction of the PCDDs and PCDFs content before dumping. Inertization is brought about by extraction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, in Colombia fly ash is mixed with household waste and landfilled without either previous treatment or use of appropriate human protection. Although characterization studies also reveals that the levels of dioxins in fly ash vary widely depending on specific combustion parameters, particle size and the air pollutant control device (APCD) used for dust collection [19,21] and [25], 1-3 ng I-TEQ/g of PCDD/Fs is accepted as an adequate value for landfill disposal in developed countries [25,26]. Nevertheless, fly ash collected from incinerators in Colombia usually contains higher dioxin concentrations [4,5] requiring additional treatment before land filling.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in Colombia fly ash is mixed with household waste and landfilled without either previous treatment or use of appropriate human protection. Although characterization studies also reveals that the levels of dioxins in fly ash vary widely depending on specific combustion parameters, particle size and the air pollutant control device (APCD) used for dust collection [19,21] and [25], 1-3 ng I-TEQ/g of PCDD/Fs is accepted as an adequate value for landfill disposal in developed countries [25,26]. Nevertheless, fly ash collected from incinerators in Colombia usually contains higher dioxin concentrations [4,5] requiring additional treatment before land filling.…”
Section: Introductionmentioning
confidence: 97%
“…Several methods for dioxin detoxification of incineration fly ash have been proposed both in solid phase [26][27][28][29][30][31][32][33] and in liquid fly ash extracts [34][35][36][37]. Among them, liquid phase catalytic hydrodechlorination (LP-HDC) over Pd supported catalyst is a promising technique for fly ash dioxin degradation since high conversions are obtained after short reaction times under moderate reaction conditions [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Extraction temperature is an important operating condition for both analytical and remediation SFE. The critical temperature of carbon dioxide is 31" C. Based on previous bench-scale studies and engineering design [6,11,151, the extraction temperature was set at either 40" C or 80" C. Table 2 shows that high temperature did slightly improve the extraction efficiency. When the extraction temperature was increased from 40" C to 80" C, 2CBP recoveries increased about 4 to 7%.…”
Section: Temperature Effectsmentioning
confidence: 99%
“…The effects of extraction pressure on PCB extraction have also been studied by several authors in bench-scale extraction [6,11,221. The common pressure range is 1,500-6,000 psi for these studies.…”
Section: Pressure Effectsmentioning
confidence: 99%
“…Recently published papers concerning process-scale studies have shown the usefulness of SFE for the remediation of soil (Zaragosa et al, 1998), decontamination of fly ash (Gabarra et al, 1999), and removal of oil for recycling of steel (Fu et al, 1998). Thus, the development of a large-scale process for the extraction of pesticides from a solid matrix as dust waste seems to be possible.…”
Section: Introductionmentioning
confidence: 99%